PERTANGGUNGJAWABAN HUKUM TERHADAP KEBEBASAN MENGELUARKAN PENDAPAT DIMUKA UMUM - Muliadi Muliadi (Maleo Law Journal, 2019)
Freedom of speech in public both verbally and in writing as well as freedom to organize are the rights of every citizen that must be recognized, guaranteed and fulfilled by the state, forms of public expression can be carried out with demonstrations or demonstrations, marches, public rallies, or free speech Therefore, our laws and regulations have provided clear protections and restrictions on freedom of expression to avoid arbitrariness. So that freedom of expression in public does not harm the concept of democracy, everyone must respect the rights and freedoms of others, respect moral rules that are generally recognized, obey the laws and regulations of applicable laws, maintain and respect public security and order; and maintain the integrity of national unity Keyword: Issue Opinion. Legal Liability. In public